Effect of Infrared Radiation (IRR) on Patients with Bell’s Palsy - Banu, Hashina Bilkish; Rahman, Sohely; Hossain, Shahadat; Jebunnesa, -; Khan, Ehsanul Haque; Mahmood, Khurshid; Rahman, DM Lutfur; Ahmed, Monjur (Bangladesh Medical Journal, 2017)
This prospective study was conducted to determine the effect of Infrared Radiation on the patients presented with Bell’s palsy attended at the Department of Physical Medicine and Rehabilitation, Dhaka Medical College Hospital (DMCH), Dhaka, Bangladesh from January 2012 to June 2012. By dividing in equal two groups ‘A’ and ‘B’ (30 patients in each group) a total of sixty (60) patients with Bell’s palsy were included in this study according to the selection criteria. Group- A patients were received Infrared Radiation (IRR) including Proprioceptive Neuromuscular Fascilitation (PNF) exercise, Drugs (Prednisolone & Acyclovir) and Counseling for their recovery, where Group- B didn’t receive IRR but received rest of management. In Group- A, 25(83.33%) patients recovered completely and among them 12 (40%) patients recovered early (within 2 months). In Group- B, 23(76.67%) patients recovered completely, among them 7 (23.33%) patient recovered early. The difference was statistically significant. The outcome of early recovery is better with the patients treated with combined effect of IRR, PNF exercise and drugs compared with combined effect of PNF, exercise & drugs. The patients who attended with facial nerve paralysis House-Brackmann (HB) Grade IV to VI during initial presentation have reduced chance of full recovery of facial nerve paralysis. Bangladesh Med J. 2017 Jan; 46 (1): 1-6